Jimmy Carter American moralist - Morris, Kenneth E. (Univ. of Georgia Press, 1996)
Jimmy Carter, American Moralist is the first full-scale biography of Carter since 1980. Drawing from scores of interviews and other primary sources, Kenneth E. Morris follows Carter from his southern roots through his naval service and political career to the international projects of the Carter Center. All of the major episodes of his life are here, including some not previously covered and many others that have been given fresh interpretations. The portrait that emerges is of a man influenced by his early life in a fragmented family and segregated community, a man whose truly remarkably career has been driven by a synthesis of evangelical, populist, and universalistic convictions. Yet we also see more clearly than ever before an individual whose moral outlook was so uncritically and perhaps unconsciously held that he could not appreciate its limitations. Through film and popular music, personality profiles and campaign summaries, poll findings and landmark court decisions, Morris sheds light on the cultural forces that shaped Carter and produced the troubled society that made him president. This mix of biography and social history is especially telling when Morris situates the Carter presidency in the "malaise" of the late 1970s. Any conclusions about Carter's leadership and its adequacy to his challenges as president, Morris shows us, cannot ignore the moral quandary that vexed the nation not only under Carter but ever since. Thus, Carter's story is the moral story of our times, and in asking not whether Carter is "good" but whether he has been good for America, we see the promises and pitfalls of our common values.